Сильно сходящийся метод расщепления для системы операторных включений с монотонными операторами - Семенов, В.В. (Проблемы управления и информатики, 2014)
Запропоновано новий алгоритм розв’язання системи операторних включень з монотонними операторами, що діють в гільбертовому просторі. Алгоритм базується на двох відомих методах: алгоритмі розщеплення Ценга та варіанті алгоритму Гальперна для апроксимації нерухомих точок скінченної сім’ї нерозтягуючих операторів. Доведено теорему про сильну збіжність породжених алгоритмом послідовностей. A novel algorithm for solving a system of operator inclusions with monotone operators acting in a Hilbert space is proposed. The algorithm is based on two well-known methods: Tseng splitting algorithm and version of Halpern algorithm for approximation of common fixed points of a finite family of nonexpansive operators. A theorem on the strong convergence of the sequences generated by the algorithm is proved.